2023
DOI: 10.1113/jp285104
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional analysis of salivary intercalated duct cells reveals a secretory phenotype

Amanda M. Wahl,
Takahiro Takano,
Shan Su
et al.

Abstract: Currently, all salivary ducts (intercalated, striated and collecting) are assumed to function broadly in a similar manner, reclaiming ions that were secreted by the secretory acinar cells while preserving fluid volume and delivering saliva to the oral cavity. Nevertheless, there has been minimal investigation into the structural and functional differences between distinct types of salivary duct cells. Therefore, in this study, the expression profile of proteins involved in stimulus–secretion coupling, as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Although the primary function attributed to salivary gland ionocytes is maintaining the ionic composition of saliva, whether they contribute directly or indirectly to saliva production is unknown. A recent report has suggested that intercalated duct cells, which were assumed to only function in maintaining the ionic composition of saliva, have properties of secretory cells and might contribute towards saliva production [ 42 ]. The i-sg -Sod2 KO model will be a valuable tool for further investigating the role of ionocytes in salivary gland function.…”
Section: Discussionmentioning
confidence: 99%
“…Although the primary function attributed to salivary gland ionocytes is maintaining the ionic composition of saliva, whether they contribute directly or indirectly to saliva production is unknown. A recent report has suggested that intercalated duct cells, which were assumed to only function in maintaining the ionic composition of saliva, have properties of secretory cells and might contribute towards saliva production [ 42 ]. The i-sg -Sod2 KO model will be a valuable tool for further investigating the role of ionocytes in salivary gland function.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the elevation in Ca 2+ was maintained throughout the period of nervous stimulation. The Ca 2+ signals were potentiated by the acetylcholinesterase inhibitor physostigmine (Takano et al., 2021) and inhibited by atropine (Wahl et al., 2023), confirming the preeminent role of acetylcholine in mediating the response. At frequencies higher than 10 Hz, while Ca 2+ peaked rapidly at higher levels, the signal was not maintained and rapidly decayed.…”
Section: Introductionmentioning
confidence: 86%
“…Indeed, GCaMP6f fluorescence could be observed in ID, SD cells, as well as acinar cells giving a unique opportunity to observe Ca 2+ signalling in vivo at physiologically relevant stimulus strengths in acinar and various duct cells, simultaneously. Notably, in intact SMG during nerve stimulation ID cells exhibited Ca 2+ transients with a magnitude and profile similar to acinar cells, while SD cells were largely refractory to stimulation at all but maximal stimulation strengths (Wahl et al., 2023) (Fig. 4).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…A week before the DMXAA or 5% sodium bicarbonate injections, tamoxifen (Sigma-Aldrich; T5648) was given to the mice via oral gavage at a dose of 0.25 mg/g of body weight for 3 consecutive days to excise the loxP sites flanking the STOP codon allowing expression of the Ca 2+ indicator within salivary glands. The mice were anesthetized and gland-exposed, as described previously (Takano et al, 2021; Takano & Yule, 2022; Wahl et al, 2023). The immobilized gland was secured within the holder using a cover glass and maintained in Hank’s salt solution (HBSS).…”
Section: Methodsmentioning
confidence: 99%